1999
DOI: 10.1016/s0014-5793(99)00818-2
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo effects of glucocorticoids on gene transfer to skeletalmuscle

Abstract: As a pharmacological approach to potentially improve gene transfer efficiency into skeletal muscle cells, glucocorticoids were shown here to allow efficient transfection of cultured and mouse human myoblasts, human pulmonary A549 cells, but not dog myoblasts, independently of the transfection protocol, the reporter gene and the transcription promoter employed. Transduction with adenovirus was also increased by dexamethasone. Pretreatment of cells 48 h prior to transfection was most effective and was shown to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…While DEX and other steroids have been used to increase nonviral gene delivery efficiency in several cell types before this study, other cell types generally show only moderate transgene expression increases (i.e. 2-4-fold increases relative to VC; Bernasconi et al, 1997;Braun et al, 1999;Chen et al, 2011;Choi & Lee, 2005;Jain et al, 1999;Koster et al, 2002;Köster et al, 2006;Lin et al, 2003;Nair et al, 2002) compared to those seen here in hMSCs. Although DEX increased transgenic luciferase activity normalized to total protein by about 10-fold in transfected hMSCs, DEX only increased the amount of transgenic luciferase protein by about two-fold, as quantified by western blot analysis normalized to total protein (Figure 1c,d), suggesting that DEX-priming somehow increases transgenic enzyme activity downstream of transgenic protein synthesis.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…While DEX and other steroids have been used to increase nonviral gene delivery efficiency in several cell types before this study, other cell types generally show only moderate transgene expression increases (i.e. 2-4-fold increases relative to VC; Bernasconi et al, 1997;Braun et al, 1999;Chen et al, 2011;Choi & Lee, 2005;Jain et al, 1999;Koster et al, 2002;Köster et al, 2006;Lin et al, 2003;Nair et al, 2002) compared to those seen here in hMSCs. Although DEX increased transgenic luciferase activity normalized to total protein by about 10-fold in transfected hMSCs, DEX only increased the amount of transgenic luciferase protein by about two-fold, as quantified by western blot analysis normalized to total protein (Figure 1c,d), suggesting that DEX-priming somehow increases transgenic enzyme activity downstream of transgenic protein synthesis.…”
Section: Discussionmentioning
confidence: 64%
“…In hMSCs, derived from bone marrow stromal cells (BMSCs) of multiple donors, we showed that 90 to 360 nM dexamethasone (DEX), a Gc drug, delivered 0-30 min before delivery of pDNA lipoplexes increased the transgenic luciferase activity about 10-fold, increased transgenic enhanced green fluorescent protein (EGFP) mean fluorescence intensity of transfected cells about two-fold, increased transfection efficiency about three-fold (i.e., percent of EGFP + transfected cells), increased duration of transgene expression, and ameliorated transfection-induced metabolic decline, all while retaining differentiation capacity (Kelly, Plautz, Zempleni, & Pannier, 2016). glucocorticoids, estrogens, and progesterone) has generally shown moderate increases in gene delivery to a wide variety of cell types (i.e., 2-4-fold transgene expression increases; Bernasconi et al, 1997;Braun et al, 1999;Chen, Shank, Davis, & Ziady, 2011;Choi & Lee, 2005;Jain, Seth, & Gewirtz, 1999;Koster et al, 2002;Köster et al, 2006;Lin et al, 2003;Nair, Rodgers, & Schwarz, 2002), with a few exceptions (i.e., 10-fold increase in myoblasts; Braun et al, 1999) and 900-fold increase in bronchial epithelial cells (Wiseman, Goddard, & Colledge, 2001). For example, priming of various cell types with steroids (i.e.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…299 Dexamethasone dilates the nuclear pores, which can also promote the nuclear uptake of large plasmid DNA and increase the transfection efficiency. 302,328,329 For researchers endeavoring to improve the nuclear uptake of DNA cargo with polymer-based vehicles, it would be helpful to understand what levels of nuclear uptake are typically achieved with standard PEI-based transfections. Using quantitative polymerase chain reaction measurements, Szoka et al detected as few as 75 and as many as 50 000 plasmid copies (<5% of the applied dose) in the nuclei of transfected cells but found that levels above 3000 plasmids/nuclei yielded marginal returns in transgene expression.…”
Section: Intracellular Barriersmentioning
confidence: 99%